A randomized comparison of three early medical abortion regimes: Mifepristone and misoprostol, misoprostol alone and methotrexate and misoprostol - Renuka Brijwal,; Nirmala Duhan,; Parul Bhugra, (Asian Journal of Medical Sciences, 2025)
Background: Abortion is defined as the spontaneous or induced termination of pregnancy before fetal viability. It is extremely likely that couples will experience at least one unwanted pregnancy at some time during their reproductive years. Majority of abortions are performed in the first trimester.Aims and Objectives: The aim of the study was to evaluate and compare the efficacy and adverse effect profile of three regimes for medical abortion up to 56 days of gestation, that is, mifepristone and misoprostol, misoprostol alone and methotrexate and misoprostol.Materials and Methods: Ninety women attending the outpatient department for the purpose of medical abortion up to 56 days of pregnancy were enrolled for the study and divided into three groups. Group I received mifepristone and misoprostol. Group II received misoprostol alone and Group III received methotrexate and misoprostol. All women were followed up on day 14 and day 28 and assessed for completeness of abortion, side effects and complications, if any.Results: Four women (13.33%) in Group I, seven (23.33%) in Group II and 16 (53.33%) in Group III needed surgical evacuation as medical termination was unsuccessful. Nausea, vomiting and fever were the most common side effects in the study.Conclusion: The regime of mifepristone and misoprostol was found to be the most efficacious of the three regimes studied. All the regimes were safe as they did not result in any major complication.